Government expenditure ceiling and public debt dynamics in a demand-led macromodel. Issue 3 (3rd July 2019) - Ribeiro, Rafael S. M.; Lima, Gilberto Tadeu
Abstract: This article explores some key aspects of the debate about the potential efficacy of a fiscal rule that sets a government expenditure ceiling for the stabilization of the public debt-to-output ratio. We develop a demand-led macromodel that assumes a closed economy operating with excess productive capacity and show that a fiscal rule that sets a limit for government spending, excluding the payment of interests, may not ensure a non-explosive trajectory of the public debt-to-output ratio. Our model allows us to map out different outcomes in terms of the stabilization of the public debt stemming from the process of fiscal consolidation and conclude that the commitment of the fiscal authority to comply with the ceiling by cutting government spending is less likely to stabilize the public debt-to-output ratio in economies enduring excessively high interest rates accompanied by more regressive taxation systems. Our model also suggests that a more progressive tax structure may often increase the chances of achieving public debt stabilization in the long run.